USE OF NEGATIVE SENTENCE IN LANGUAGE MONGONDOW, MONGONDOW DIALECT - Sri Diharti (Pusbindiklat - LIPI, 2013)
his research aims to describe about markers and use of negative sentence in language Mongondow, Mongondow dialect. The source of research data is oral data (primary) that writer get in the field research and obtained directly from informant as native speaker. This type of research is descriptive, that is explained in accordance with what is obtained. The data analysis techniques used is the ellipsis technique which is used to determine the role of negative markers, expansion technique is used to determine levels of the possibility of negative markers can be expanded or not, and permutation technique is used to locate or position may be assigned negative markers. The results of this research found a constituency that is used as negative markers in declarative negative sentence and interrogative language Mongondow, Mongondow dialect is jia’ ‘no’, jia’moibog ‘no way’, jia’dega ‘impossible’, and deeman ‘not’, then dika negative imperative sentence constituent is ‘don’t’.